Development of the prototype of the digital form for Studies in Food, Nutrition, Health and Aging: EANSE FORMS (Research, Society and Development, 2021)
The objective was to describe the methodological and prototyping process of the digital form for studies on food, nutrition, health and aging: Eanse Forms. This is a quantitative study, with a cross-sectional design and descriptive approach of the development of a process of the prototype of the digital form, Eanse Forms, which aims to collect, store, structure and export data on health and food consumption of the elderly. The form is composed of questions, including a 24-hour recall to evaluate food intake. Its development was structured in six stages. In the last one, a pre-test was conducted on forty-five elderly volunteers in October and November 2019. The form was applied individually, through a guided interview, with the presence of previously trained nutritionists. At the end, aspects such as acceptance of the form, understanding of the questions, interview time, suggestions, and necessary adjustments were evaluated. The results of the pre-test showed that the performance of the form was considered satisfactory and was well accepted by the participants. However, it is worth emphasizing that the wider and more effective use of the form still depends on new rounds of analyses, including evaluations of the structure, the incorporation of suggestions and adjustments identified in the pre-test, and the validation study itself. It is believed that the next steps will allow obtaining a digital form, of free access and able to collect, store, structure and export data on food, nutrition, health and aging. Thus, it is expected that the digital form, Eanse forms, will provide subsidies to develop health promotion actions for the elderly population.